Influence of carpal–ulnar translation on clinical outcome after scaphocapitate arthrodesis for the treatment of late-stage Kienböck disease. Issue 1 (January 2022) - Park, Ji Hun; Kang, Jong Woo; Choi, Jeong Seok; Kim, Dongmin; Choi, In Cheul; Park, Jong Woong
ABSTRACT: Background: This study sought to compare postoperative outcomes after scaphocapitate arthrodesis (SCA) for the treatment of late-stage Kienböck disease according to the amount of ulnar translation of the carpus and to identify surgical factors associated with carpal–ulnar translation. Methods: Thirty-nine patients diagnosed with Kienböck disease (Lichtman stages III-IV) and treated with SCA were retrospectively reviewed. They were divided into the translated group (n=28) and untranslated group (n=11) according to the presence of carpal–ulnar translation. The following surgical factors in the patients were assessed: excision of the lunate, postoperative carpal height ratio, and radioscaphoid angle (RSA). Pain Visual Analog scale (VAS) score, wrist range of motion, grip strength, modified Mayo wrist score (MMWS), the Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH) score, and progression of radioscaphoid osteoarthritis were also assessed. Results: All patients showed functional improvement after a mean postoperative follow-up period of 40 months (VAS: 4.1 vs. 1.1, p <0.001; grip strength, 42.3 vs. 51.2 lb., p = 0.002; MMWS, 52.6 vs. 69.5, p <0.001; QuickDASH, 33.7 vs. 21.5, p <0.001). No statistically significant differences were found between the two groups in terms of outcome measures. Among the assessed surgical factors, the mean postoperative RSA was significantly smaller in the translated group than in the untranslated group (34.8° vs. 46.8°, p = 0.008). The proportion of patients with postoperative RSA <30° was significantly higher in the translated group than in the untranslated group (54.5% vs. 0%, p<0.001). Conclusion: These results suggest that sufficient pain relief and functional improvement can be achieved after SCA for the treatment of late-stage Kienböck disease disregarding the occurrence of carpal–ulnar translation. In this study, overcorrection to RSA <30° induced more frequent carpal–ulnar translation after SCA.